Biobased long-chain aliphatic polyesters of 1, 12-dodecanedioic acid with a variety of diols: Odd-even effect and mechanical properties. (June 2019) - Zhou, Changfeng; Wei, Zhiyong; Yu, Yang; Shao, Shengnan; Leng, Xuefei; Wang, Yanshai; Li, Yang
Graphical abstract: Highlights: Biobased long-chain aliphatic polyesters with 1, 12-dodecanedioic acid and various diols were synthesized. Thermal and mechanical properties depend on the chain length of diols and display even-odd effect. Poly(ethylene dodecanedioate) and poly(propylene dodecanedioate) were peculiar. A PE-like mechanical property with appropriate tensile strength and excellent elongation. Abstract: A series of biobased long-chain aliphatic polyesters with high molecular weight were synthesized by a two-step process of esterification and polycondensation from 1, 12-dodecanedioic acid and diols with nine different carbon chain lengths from C2 to C10. The influences of the chain length of diols and its even-odd effect on the chemical structure, basic thermal properties and thermal stability, crystalline structure and morphology, as well as mechanical properties of the obtained polyesters were systemically investigated. Besides the common even-odd effect was observed impacting on the thermal properties, it was found that poly(ethylene dodecanedioate) (P2D) and poly(propylene dodecanedioate) (P3D) were peculiar in thermal properties and thermal stability as well as crystalline structure and morphology, probably due to their the unique short chain conformations. Furthermore, these polyesters showed PE-like mechanical properties with appropriate tensile strength and excellent elongation depending on the used diols. The elongation at break of the odd-numbered series was significantly longer than that of the even-numbered series, of which poly(nonylene dodecanedioate) (P9D) has the highest elongation at break, up to 1972%.